Job Demands to Turnover Intention: A Systematic Literature Review - Liyanti, Aisyah Febri (Universitas Batanghari, 2024)
The purpose of this article is to systematically review existing research on job demands to turnover intention. The aims of this study are to bridge the gap between job demands and turnover by systematically review the main issues from previous research finding regarding the correlation of job demands to turnover intention. All articles that cited the Job Demands and Turnover have been systematically reviewed. In total, 13 studies of 394, found in Scopus are included in the review.Â The findings from our study indicate that High job demands have a positive influence on increasing turnover intentions. Physical and psychological fatigue and burnout are indicators of the effects of high job demands. This paper evaluatesÂ the comprehension of high job demands to turnover intention.